Simultaneous regulation of both lignin and cellulose biosynthesis modifies xylem fiber properties in Populus - Jian Li; Yu Han; Yu Han; Xianwen Lu; Xinwei Tang; Jiayan Sun; Meng Li; Laigeng Li (Frontiers in Plant Science)
IntroductionWood is primarily made up of secondary xylem cell walls, with lignin, cellulose, and hemicellulose as the main chemical components. The presence of lignin represents recalcitrance to wood pulping and biofuel conversion. Consequently, reducing lignin content is a key approach to improving wood properties and optimizing its processing.MethodsIn this study, we suppressed lignin biosynthesis by overexpressing a mutated transcription repressor PdLTF1AA and enhanced cellulose synthesis simultaneously by introducing cellulose synthase genes, PdCesA4, PdCesA7A, or PdCesA8A, specifically in xylem fiber cells.Results and discussionThe transgenic plants exhibited decreased lignin content and a significant increase in cellulose content. Transcriptome analysis indicated that expression of PdLTF1AA along with PdCesA4, PdCesA7A, or PdCesA8A in fiber cells resulted in transcriptional alterations in the genes associated with cell wall remodeling and polysaccharide synthesis during xylem development. The results also indicated that the diameter of wood fiber cells within the xylem is increased, which leads to a larger stem diameter in the transgenic plants. This study suggests that the biosynthesis of lignin and cellulose can be simultaneously modified, which presents a new strategy for modifying wood fiber characteristics for more efficient fiber and biomass processing.